A Comprehensive Analysis of The Literature Concerning the Performance of Mutual Funds in India - Palash Sharma; Dr. R. Shridhar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
According to AMFI, a mutual fund is a collective investment scheme managed by a skilled Fund Manager who oversees a pool of funds. A trust is formed to gather small deposits from various individuals with a common financial goal. These pooled funds are then invested in a diversified portfolio of securities, including equities, debt, and money market instruments. Individual investors often struggle to achieve substantial returns in the stock market due to limited expertise and capital, which hinders proper diversification. Mutual fund companies address these challenges by aggregating small investments from multiple investors and diversifying the portfolio effectively. Numerous studies have been conducted on the financial performance of mutual funds in India. Most researchers used traditional statistical and financial tools to assess risk and return for various schemes. These tools were also employed to compare schemes across different mutual fund companies. Researchers examined a broad range of sample systems, offering insights into their practicality and recommending improvements. Investigations have also focused on identifying the factors influencing mutual fund purchases and understanding the decision-making processes behind these investments. Some studies concentrated on analyzing the stock selection and timing abilities of mutual fund companies, while others compared the performance of schemes offered by public and private sector mutual fund companies.